The SEDIMENTOLOGICAL ANALYSIS, DEPOSITIONAL ENVIRONMENT AND SEQUENCE STRATIGRAPHIC STUDY OF IDA 4, 5, 6 WELLS NIGER DELTA BASIN, NIGERIA - Chukwuma-Orji, Jacinta Nkiru (FUDMA JOURNAL OF SCIENCES, 2023)
Sequence stratigraphic study divides sedimentary successions into unconformity or maximum flooding surface bounded units (sequence) that form during a single, major cycle of sea-level change. Detailed sedimentological and sequence stratigraphic studies of the strata penetrated by Ida-4, 5, and 6 wells were carried out to deduce the depositional environment and correlate the stratigraphic units. The wells are located in the coastal swamp depobelt of the Eastern Niger Delta. Studied samples were dry-sieved for sedimentological analyses. Each fraction was studied under reflected light microscope. The lithology consists of an alternation of shale and sandstone units. The grain size of the sandstone units consists of fine to medium grains, occasionally coarse to granule-sized grains. Dominant accessories minerals are ferruginous materials, shell fragments, carbonaceous detritus, and few records, of mica flakes, glauconite, and pyrite. Regular sand and shale intercalation pattern on the Gamma Ray log permitted easy recognition of sub-cycles (autocycles) of sedimentation in an extensively developed paralic sequence. Paleoenvironmental reconstruction using accessories minerals recognizes shallow water settings with intermittent deeper water conditions. Rapid sedimentation rates are inferred in the studied area based on the observed alternation of thick sandstone, shale, and mudstone units. The MFS and SB were dated 9.5 Ma and 10.35 Ma respectively. Lithologic and system tracts correlations show lateral continuity of sandstone units (potential reservoirs) depicted in the lithofacies subcycles correlation. This is useful in the determination of reservoir geometry, areal coverage, and calculation of the volume of accumulated hydrocarbon, and directing well trajectory during the drilling operation.